SAFE DEPOSIT BOX SYARIAH SERTA KESESUAIANNYA DENGAN FATWA DSN MUI NOMOR. 24 TAHUN 2002 (Kajian di Bank Syariah Mandiri Kantor Cabang Bintaro Kota Tangerang Selatan Provinsi Banten) - Ansori, Mohammad; Khusnul Khotimah, Umi; Hidayat, Hidayat; Ramadhan, Taufiq (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2021)
Starting from a study written by Widodo in his thesis which states that the application of the contract used in the Safe Deposit Box product, in practice uses several contract agreements, while the DSN-MUI Fatwa on sharia Safe Deposit Box products only uses one contract, namely ijarah. This study uses a comparative descriptive method, while the data sources listed are the results of data obtained from direct interviews with staff and the head of the BSM Bintaro branch, as well as documents from Bank Mandiri Syariah Bintaro Branch Office, South Tangerang City, DSN-MUI Fatwa Sheet regarding Safe Deposit Box Products. The results of this study indicate that: First, Bank Syariah Mandiri Bintaro applies a Safe Deposit Box, using a lease contract (Ijarah) and several accompanying contracts, namely the wadi'ah yad-dhamanah contract and the Rahn contract (Guarantee). Second, this is different from the DSN-MUI Fatwa which states that the contracts used by Safe Deposit Box products only use ijarah contracts. Bank Syariah Mandiri Bintaro implemented the ijarah contract as the main contract in accordance with the DSN-MUI fatwa, then Bank Syariah Mandiri Bintaro added the wadi'ah yad-dhamanah (deposit) and Rahn (guarantee) contracts. The ijarah agreement in accordance with the DSN-MUI Fatwa is used for the rental of the Safety Deposit Box; The wadi'ah yad-dhamanah (deposit) contract is used for the safekeeping of the contents of the box (the goods), while the rahn (collateral) contract is used to guarantee the keys/locks of the Safe Deposit Box